Pengaruh Dosis Probiotik Pro Top Terhadap Laju Pertumbuhan Ikan Nila (Oreochromis Niloticus) pada Sistem Bioflok di Minadesa Fishfarm - Muhammad Izzat Ardiansyah; Indra Wirawan; Maria Agustini (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Biofloc technology is a super-intensive fish cultivation method, which benefits heterotrophic bacteria to harvest organic chemical compounds and amines from fish metabolic residues to be converted into bacterial proteins. The use of probiotics is very important to be carried out in cultivation activities, Probiotics are living microorganisms that have a beneficial effect on humans by balancing the microflora in their intestines. The bacteria in probiotics have a mechanism in forming several enzymes for feed digestion. This study aims to determine the effect of administering Pro Top probiotics with different doses on the absolute weight growth of tilapia (Oreochromis niloticus). Probiotics are mixed with feed with a biofloc cultivation system. The method used in this study is an experimental method with a Completely Randomized Design (CRD) with 4 treatments and 6 replications, namely by adding different doses to the treatment. Treatment A (0.5 grams / kg), B (1 gram / kg), C (2 grams / kg) and D (5 grams / kg). The parameters observed are absolute weight growth. Supporting parameters for air quality are temperature, pH, and DO. Data were analyzed using the ANOVA test. Based on the results of the study, it shows that administering different doses of Pro Top probiotics has a significant effect on the absolute weight growth of tilapia (Oreochromis niloticus). Treatment A (0.5 grams/kg) gave the lowest absolute weight growth of 31.05 grams and treatment D (5 grams/kg) gave the highest absolute weight growth of 40.30 grams. Air quality parameters including air temperature ranged from 25.3 – 26.1°C, acidity level around 7.5 – 8.0. And dissolved oxygen ranged from 4.7 – 5.3 ppm. The results of the analysis of variance (ANOVA) of the three air quality parameters showed no difference between the treatments of tilapia (Oreochromis niloticus).